Dukungan Sosial Terhadap Anak Broken Home Dalam Pemberdayaan Masyarakat Di Desa Onto Kecamatan Bontomatene Kabupaten Kepulauan Selayar - Ariani, Andi Erni; Hamriani,; Tahir, Qaharuddin (Jurnal Berita Sosial, 2025)
The main problem in this study is How is Social Support for Broken Home Children in Community Empowerment in Onto Village, Bontomatene District, Selayar Islands Regency. From the main problem, the researcher puts forward two sub-problems as follows: 1) how is the behavior of broken home children in Onto Village, Bontomatene District, Selayar Islands Regency? and 2) what form of social support is given to broken home children in community empowerment in Onto Village, Bontomatene District, Selayar Islands Regency? This type of research is qualitative research with a sociological approach. The data sources for this study are primary data and secondary data. Furthermore, the data collection methods used are observation, interviews and documentation. Then, data processing and analysis techniques are carried out with the stages of data reduction, data presentation and drawing conclusions. The results of the study showed that the behavior of broken home children in Onto Village, Bontomatene District, Selayar Islands Regency is; 1) children become more independent, children have difficulty managing emotions, lose motivation to learn, and children become depressed and always hopeless. 2) Forms of social support given to children from broken homes include: emotional support, appreciation support, instrumental support, and informative support. The implications of this study indicate that social support from family and society plays an important role in helping children from broken homes adapt and develop positively. Therefore, attention from parents, community concern, and support from the government in the form of empowerment and mentoring programs for children from broken homes are needed.